Case Report: Development of persistent genital arousal disorder due to a possible combination of medications - Fiala, Ludek; Lenz, Jiří (Frontiers in Psychiatry, 2025)
ObjectivePersistent Genital Arousal Disorder (PGAD) is a rare and distressing condition characterized by persistent genital arousal in the absence of sexual desire. We present a unique case of a menopausal woman who developed PGAD after combined pharmacotherapy with trazodone, pregabalin, vaginal estriol, and depot medroxyprogesterone acetate (DMPA).MethodsThe patient underwent comprehensive gynecological, neurological, and psychiatric evaluation. Menopausal status was confirmed by laboratory findings. A detailed pharmacological review was conducted to assess possible interactions affecting serotonergic, neuronal, and hormonal regulation.ResultsPGAD symptoms emerged shortly after initiating the combination of these medications. Each drug has been individually associated with alterations in sexual function, but their concurrent use may have produced synergistic effects on neuroendocrine pathways. Gradual discontinuation of all medications resulted in complete remission of symptoms.ConclusionThis case supports the hypothesis that combined modulation of serotonergic, neuronal, and hormonal systems can trigger PGAD in predisposed menopausal women. Recognition of potential pharmacological interactions is crucial for diagnosis and management of PGAD.